The Clinical and Electrophysiological Features in Patients with Wolff- Parkinson- White Syndrome - Dhungana, Murari; Rajbhandari, Sujeeb; Shaha, Kunal Bikram; Sharma, Mukunda; KC, Man Bahadur (Nepalese Heart Journal, 2014)
Background and Aims: Wolff-Parkinson-White Syndrome is a congenital anomaly with delta wave in electrocardiogram representing an accessory conducting pathway. The aim of the present study was to evaluate the characteristic features of patients who underwent electrophysiological study and radiofrequency ablation at Shahid Gangalal National Heart Centre. Methods: One hundred ninety eight patients with Wolff-Parkinson-White syndrome were divided in to three age groups; 1) 8 to 17, 2) 18 to 29 and 3) 30 to 70 years. The clinical, electrophysiological and therapeutic data of these patients were taken retrospectively from the hospital records. Result: A total of 10 (5%) of these patients were less than 18 years of age. There was no sex difference in group 1 and 2. There were significantly more male patients in group 3. There were fewer patients with left sided accessory pathway in group 1 compared to group 2 and 3 (p=0.024 and p=0.002, respectively). Conclusion: This study describes several different electrophysiological characteristics in patients with Wolff-Parkinson-White syndrome. The study showed that the detection of left side accessory pathway was less frequent in children and adolescents with Wolff-Parkinson- White syndrome as well as no gender preponderance in this age group. Nepalese Heart Journal | Volume 10 | No.1 | November 2013| Pages 17-19 DOI: http://dx.doi.org/10.3126/njh.v10i1.9741